Pattern of epidemiological correlates among road traffic accident in-patients of a tertiary care hospital of West Bengal, India - Mitra, Satabdi; Saha, Indrajit; Haldar, Dibakar; Sarkar, Adiyta Prasad; Sarkar, Gautam Narayan (International Journal Of Community Medicine And Public Health, 2018)
Background: Road traffic accident (RTA) is an emerging epidemic of current century perpetrated by a complex interaction of human, vehicle and roadways/environmental factors. The current study was conducted to find out the various determinants of outcomes of RTAs in a district of West Bengal, India. Methods: A cross-sectional study was conducted over one year by face-to-face interviewing 384 RTA in-patients of departments of General Surgery and Orthopedics of a rural tertiary level hospital of West Bengal, India selected via scheduled sampling. Information pertaining to demographic and correlates of RTA were collected. Follow-up telephonic interview was conducted after one month for ascertaining the final outcome. There were 16 non-respondents in the 2nd phase who were excluded during final compilation rendering the sample size to 368. With SPSS version 22.0, descriptive and inferential statistical analyses were done. Results: 13.2% and 21.0% of study participants had death and disability respectively. On multinomial logistic regression assuming complete cure as reference outcome, both death and disability were revealed to have significant (<0.05) association to non-usage of protective devices, time of incidence (6AM to 6PM), poor road condition, sustaining multiple injuries and lapsing ‘golden hour’ for treatment. Conclusions: Stringent enforcement of legislations regarding various road safety measures, improving ply-worthiness of roads and establishment of trauma care centre at the district are essential to induce road “safe systems”.